DINAMIKA KEWIRAUSAHAAN DI KAWASAN PERBATASAN POS LINTAS BATAS NEGARA ARUK: PROFIL WIRAUSAHA LOKAL DI SAJINGAN BESAR DAN PENGARUH PLBN TERHADAP PERTUMBUHAN USAHA PERDAGANGAN DAN JASA - Riki Humaidi; Oskar Hutagaluh; Desi Yuniarti (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2026)
This study aims to analyze the dynamics of local entrepreneurship in Sajingan Besar District, a border economic area, and to examine the influence of the Aruk Cross-Border Post (PLBN) on the emergence of new businesses in the trade and services sectors. Furthermore, this study assesses the role of training and empowerment facilitated by the National Border Management Agency (BNPP) in fostering community entrepreneurial capacity. The study used a qualitative approach with descriptive methods through interviews, observation, and documentation with local business actors, village officials, PLBN managers, and entrepreneurship training participants. The results indicate that the Aruk PLBN serves as a growth pole, encouraging the emergence of trade kiosks, transportation services, culinary delights, and lodging businesses. Key driving factors include increased accessibility, cross-border mobility, the availability of tourist markets, and the BNPP's entrepreneurship training program. However, obstacles remain, including limited capital, business literacy, and business diversification. This study emphasizes the importance of integrating infrastructure development with local economic empowerment to create sustainable entrepreneurship in the border region.